2017
DOI: 10.17660/actahortic.2017.1150.15
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the ZIM-probe technology for detecting water stress in clementine and persimmon trees

Abstract: Further improvement on irrigation management requires continuous plant water status monitoring. The non-invasive ZIM-probe measures the pressure (Pp) transfer function through a patch of an intact leaf, which is inversely correlated with the turgor pressure. Data are sent wireless in real-time by telemetry to an Internet server via a mobile phone network where it is available to be analyzed. In this work, the detection of water stress by measuring relative changes in turgor pressure with the ZIM-probe was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Different approaches can be followed to detect plant water stress when analyzing data from the Yara ZIM-probes (Zimmermann et al 2013b). The assessment of the maximum daily P p seems to be a useful method for clementine trees, in which a half or complete inversion of the P p curve does not often occur even under severe (Ψ stem of up to −1.9 MPa) water-stressed conditions (Ballester et al 2016). Contrary to this and more in the line of what has been reported for other crops like almond, eucalyptus, avocado (Zimmermann et al 2013b) and olive trees (Fernández et al 2011;Ehrenberger et al 2012;Padilla-Díaz et al 2015), the change observed in the P p curve profile was shown as a useful method to detect drought stress in Persimmon trees.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches can be followed to detect plant water stress when analyzing data from the Yara ZIM-probes (Zimmermann et al 2013b). The assessment of the maximum daily P p seems to be a useful method for clementine trees, in which a half or complete inversion of the P p curve does not often occur even under severe (Ψ stem of up to −1.9 MPa) water-stressed conditions (Ballester et al 2016). Contrary to this and more in the line of what has been reported for other crops like almond, eucalyptus, avocado (Zimmermann et al 2013b) and olive trees (Fernández et al 2011;Ehrenberger et al 2012;Padilla-Díaz et al 2015), the change observed in the P p curve profile was shown as a useful method to detect drought stress in Persimmon trees.…”
Section: Discussionmentioning
confidence: 99%
“…Olive is cultivated in dry or semi-dry regions with limited or no irrigation water supply. LPCP probes were also related to plant water status indicators in other fruit crops, such as banana (Zimmermann et al, 2010), grapevine (Rüger et al, 2010), clementine (Ballester et al, 2017), and persimmon (Ballester et al, 2017; Martínez-Gimeno et al, 2017). However, as for fruit sensors, the use of LPCP probes alone can only give partial information on whole plant water status, unless many sensors are used on a tree.…”
Section: Introductionmentioning
confidence: 99%
“…Olive is cultivated in dry or semi-dry regions with limited or no irrigation water supply. LPCP probes were also related to plant water status indicators in other fruit crops, such as banana (Zimmermann et al, 2010), grapevine (Rüger et al, 2010), clementine (Ballester et al, 2017), and persimmon (Ballester et al, 2017;Martínez-Gimeno et al, 2017). However, as for fruit sensors, the use of LPCP probes alone can only give partial information on whole plant water status, unless many sensors are used on a tree.…”
Section: Introductionmentioning
confidence: 99%